Thalidomide in plasma cell balanitis refractory to conventional topical treatment - Lucas Mariano Serrão; Karina Demoner de Abreu Sarmenghi; Barbara Christina Bonino Pereira Pinto; Paulo Bittencourt de Miranda (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Zoon's plasma cell balanitis is a chronic genital inflammatory dermatosis that affects uncircumcised men, especially the elderly. It's characterized by painless erythematous plaques of orange hue, located on the glans penis and foreskin. Circumcision is the most effective treatment; however, it can be hard for patients to accept. As an alternative, topical calcineurin inhibitors are used, with good response. This article reports the case of a 32-year-old patient, HIV carrier, diagnosed with Zoon's plasma cell balanitis. Treatment with topical tacrolimus was administered, without improvement. A 6-week course of thalidomide resulted in complete remission of the lesions, without recurrence after eight months of follow-up.